Notices descriptive of the Localities of certain sculptured stone monuments in Forfarshire &c. (Part I) (Proceedings of the Society of Antiquaries of Scotland, 1858)
This article aims to shed light on some of the sculpted stone monuments of Perth, Kincardine and Angus. Taking each monument in turn, the author discusses the design of the monuments and gives a brief overview of the history of the area in which they were uncovered. Several of the monuments were discovered on or near burial sites and for some of these sites the author relates local legends about historical figures who might have been buried there. Meeting notes for March 10, 1856 are appended.